An extracellular Cu/Zn superoxide dismutase from Neocaridina denticulata sinensis: cDNA cloning, mRNA expression and characterizations of recombinant protein. Issue 128 (September 2022) - Feng, Dandan; Gao, Xi; Kong, Weihua; Wu, Zixuan; Yan, Congcong; Liu, Yujie; Xing, Kefan; Sun, Yuying; Zhang, Jiquan
Abstract: Neocaridina denticulata sinensis possesses characters of rapid growth, tenacious vitality, short growth cycle, transparent, and easy feeding. Therefore, it is gradually being developed into an animal model for basic research on decapod crustaceans. Herein, a Cu/Zn superoxide dismutase (Cu/Zn-SOD), named as Nd-ecCu/Zn-SOD, was identified and characterized from N. denticulata sinensis . The full-length cDNA sequence of Nd-ecCu/Zn-SOD is 829 bp containing a 684 bp open reading frame, which encodes a protein of 227 amino acid residues with a typical Sod_Cu domain. The quantitative real-time PCR analysis showed that Nd-ecCu/Zn-SOD mRNA was expressed in all the tested tissues. Under challenge with copper, the mRNA expression of Nd-ecCu/Zn-SOD reached the maximum at 6 h, and decreased until 24 h. After 24 h of exposure, its expression was up-regulated significantly at 36 h. After then its expression sharply decreased with a comeback at 48 h. The result indicated that Nd-ecCu/Zn-SOD might play an important role in the stress response of N. denticulata sinensis . The expression of Nd-ecCu/Zn-SOD in gills challenged with Vibrio parahaemolyticus changed in a time-dependent manner. Nd-ecCu/Zn-SOD was lowly expressed in early developmental stages by RNA-Seq technology, yet it showed that a cyclical rise and fall occurred between middle stages and late stages. In addition, Nd-ecCu/Zn-SOD was recombinantly expressed using E. coli and the recombinant protein was purified as a single band on SDS-PAGE. The recombinant Nd-ecCu/Zn-SOD (rNd-ecCu/Zn-SOD) existed enzymatic activity under a wide range of temperature and pH. The exposure of metal ions was found that Zn 2+, Mg 2+, Ca 2+, Ba 2+, and Cu 2+ could inhibit the enzymatic activity of rNd-ecCu/Zn-SOD, and Mn 2+ increased the enzymatic activity of rNd-ecCu/Zn-SOD. These results indicate that Nd-ecCu/Zn-SOD may play a pivotal role in resistant against oxidative damage and act as a biomarker under stressful environment. Graphical abstract: Image 1 Highlights: It is the first time to clarify extracellular Cu/Zn-SOD in N. denticulata sinensis. The mRNA expression profile was clarified after challenges. The mRNA expression was performed during different developmental stages of embryos. The rNd-ecCu/Zn-SOD enzymatic characterization was characterized.